PENGARUH MODEL LEARNING TOGETHER UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BOGA DASAR (SMK PGRI 3 DENPASAR) - Wintari, Ni Nengah; Suartana, I Ketut; Sentosa, Putu Pranatha (Widyadari: Jurnal Pendidikan, 2019)
The purpose of this study is 1) To improve student learning motivation by using the learning together model on basic food learning; 2) To improve student learning outcomes by using the learning together model on basic culinary learning class X 4 Catering Services SMK PGRI 3 Denpasar. This type of research is classroom action research with the Kemiss Taggart model. With descriptive quantitative data analysis techniques. The object of research is students' learning motivation and student learning outcomes and subjects in this study are students of class 4 food 4 SMK PGRI 3 Denpasar. The results of this study indicate that 1) an increase in student motivation, the increase is seen from the average percentage of the first cycle is 55.43% while in the second cycle is 80.35%, 2) the increase in student learning outcomes, the increase is seen from the average percentage of the first cycle of 70.12% while in cycle II it was 81.18%, 3) increased classical completeness, the increase was seen from the average percentage of the first cycle of 46.81% while in the second cycle was 100%. The conclusion of this study is that the application of together learning models can improve student learning motivation and student learning outcomes.